2023
DOI: 10.3390/su15043009
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Positive Electronic Word of Mouth and Purchase Intention Using Theory of Consumption Value

Abstract: Green is a timely and crucial concept in sustainability; therefore, encouraging both public and private businesses in Malaysia to persistently promote and make attempts to put green practices into effect is similarly crucial. The green industry and its environment are under pressure as a result of its acquisition, which is still occurring at an alarming rate. Using the theory of consumption values (TCV) as the underlying theory, this study explores the potential drivers of green purchases while also analyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…The spread of Word of Mouth through Internet social media is very easy, and its spread is widespread because access is relatively efficient, one of which is through the YouTube application, WhatsApp, line, google, Facebook, and other applications found on devices connected to other internet connections. This is in line with research conducted by Al-Gasawneh et al (2023), Aravindan et al (2023), andSu et al (2023).…”
Section: The Effect Of Word Of Mouth On Purchase Intentionsupporting
confidence: 92%
“…The spread of Word of Mouth through Internet social media is very easy, and its spread is widespread because access is relatively efficient, one of which is through the YouTube application, WhatsApp, line, google, Facebook, and other applications found on devices connected to other internet connections. This is in line with research conducted by Al-Gasawneh et al (2023), Aravindan et al (2023), andSu et al (2023).…”
Section: The Effect Of Word Of Mouth On Purchase Intentionsupporting
confidence: 92%
“…Hence, credible and influential eWOM is highly valued (Wang et al, 2018) and an important precursor of purchase intention (Erkan and Evans, 2016;Elhajjar, 2022;Halim and Keni, 2022;Puriwat and Tripopsakul, 2022a). Aravindan et al (2023) concluded that promoting positive eWOM by emphasizing sustainable practices sparks public interest in green purchases. Likewise, Mainardes et al (2023) found that eWOM quality and credibility shape consumer attitudes toward eWOM and purchase intention of cosmetics.…”
Section: The Relationship Between Ewom and Purchase Intentionmentioning
confidence: 99%
“…Research has demonstrated that a green brand image significantly influences the purchase intention of consumers [91][92][93]. Finally, green WOM involves consumers sharing their positive opinions regarding the environmental aspects of products, which can influence their friends, relatives, and colleagues, thereby motivating these people to purchase green products [94].…”
Section: Green Brand Image Green Wom and Consumer Purchase Intentionmentioning
confidence: 99%